Analisis Kemampuan Komunikasi Matematis Mahasiswa Melalui Penerapan Blended Learning Pada Mata Kuliah Geometri - Fadhelina, Nishbah (STKIP Yapis Dompu, 2021)
This study aims to determine how students' mathematical communication skills apply blended learning in geometry courses. This research uses a qualitative approach and descriptive research type. The instrument used was a test of mathematical communication skills. The subjects research were second semester students of the Universitas Samudra, Mathematics Education study program. The results showed that blended learning was going well, it could be seen from the average percentage of communication skills students are on the writing indicator (written text) is 90% that belongs to the category very good, drawing, is 80% which belongs to the category good and mathematical expressions is 65% that also belongs to good category,. The conclusion of this research is that blended learning can develop mathematical communication skills.